Air-borne ultrasonic application in the drying of grape skin: Kinetic and quality considerations. (January 2016) - Cruz, L.; Clemente, G.; Mulet, A.; Ahmad-Qasem, M.H.; Barrajón-Catalán, E.; García-Pérez, J.V.
Highlights: Air-borne application of power ultrasound in grape skin convective drying. Quality of dried skin determined by total phenolic content and antioxidant capacity. Temperature and ultrasound application had significant influence on drying kinetics. They also influenced the total phenolic concentration and antioxidant capacity. Abstract: The aim of this work was to address the air-borne application of power ultrasound in the convective drying of grape skin, a by-product of winemaking. For that purpose, convective drying experiments were carried out on red grape skin at 40, 50, 60 and 70 °C with (21.7 kHz, 45 W) and without power ultrasound application. The kinetic intensification was evaluated by modeling the drying kinetics using empirical and diffusion models. Meanwhile, the quality of the dried product was determined by obtaining ethanolic extracts and assessing the total phenolic content and antioxidant capacity by means of the FRAP method. Moreover, individual polyphenols were identified by HPLC-DAD-ESI-MS/MS and a Partial Component Analysis (PCA) was performed in order to elucidate the relationships between the measured variables that were related to bioactive content. Both temperature and ultrasound application had a significant ( p  < 0.05) influence on the drying kinetics, which were satisfactorily described by both the Peleg and diffusion models. In addition, both factors significantly ( p  < 0.05) influenced the total phenolic concentration and antioxidant capacity of the extracts. Ultrasound application reduced the antioxidant potential, probably due to oxidase activation and cell degradation. Bioactive potential, on the other hand, was increased as a consequence of high-temperature drying, leading in particular to a greater release of malvidin 3-O-β-D-galactoside.